Enhanced expression of PD-L1 in oral squamous cell carcinoma-derived CD11b+Gr-1+ cells and its contribution to immunosuppressive activity. (August 2016) - Fuse, Hiroki; Tomihara, Kei; Heshiki, Wataru; Yamazaki, Manabu; Akyu-Takei, Rie; Tachinami, Hidetake; Furukawa, Ken-ichiro; Sakurai, Kotaro; Rouwan, Moniruzzaman; Noguchi, Makoto
Highlights: We characterized immunosuppressive CD11b + Gr-1 + cells in oral cancer. CD11b + Gr-1 + cells in tumors expressed PD-L1 more abundantly than in the spleen. CD11b + Gr-1 + cells from tumors, but not the spleen, suppressed T cell proliferation. Summary: Cancer is often associated with dysregulation of both the humoral and cellular immune response, which in some instances is believed to result from changes in immune cell populations. For example, immunosuppressive CD11b + Gr-1 + myeloid-derived suppressor cells have been shown to proliferate in the tumor microenvironment and surrounding tissues, highlighting the relationship between tumor growth and impairment of the immune response. However, the role of myeloid-derived suppressor cells in cancer progression has not been fully characterized because these cells are heterogeneous with properties influenced by the type and location of the tumor. Here, we show that CD11b + Gr-1 + cells are elevated in the peripheral blood, spleen, and tumor of mice with oral squamous cell carcinoma. The phenotype and function of these cells varied depending on the tissue of origin. In particular, CD11b + Gr-1 + cells in tumors expressed PD-L1 more abundantly than those in other tissues. Accordingly, CD11b + Gr-1 + cells from tumors, but not from the spleen, suppressed T cell proliferation in vitro . The results suggest that tumor-derived or immune factors result in the accumulation of phenotypically and functionally diverse populations of CD11b + Gr-1 + cells in mice with oral squamous cell carcinoma. The data also indicate that PD-L1 expression in CD11b + Gr-1 + cells contributes to immune suppression, implying that targeting both myeloid-derived suppressor cells and PD-L1 would be an effective immunotherapeutic strategy against oral cancer.